2009
DOI: 10.1111/j.1748-5827.2008.00655.x
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic appearance of cardiogenic pulmonary oedema in 23 cats

Abstract: The variable appearance of feline pulmonary oedema is likely to complicate its radiographic diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
4
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 13 publications
5
41
4
1
Order By: Relevance
“…There is little literature on the CT appearance of pulmonary edema in cats, likely because most institutions and hospitals require general anesthesia, precluding CT examination. The CT findings of pulmonary edema described in our study were similar to the previously reported variable radiographic appearance of pulmonary edema in cats . This study confirms and adds to the literature of the CT appearance of pulmonary edema in cats.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…There is little literature on the CT appearance of pulmonary edema in cats, likely because most institutions and hospitals require general anesthesia, precluding CT examination. The CT findings of pulmonary edema described in our study were similar to the previously reported variable radiographic appearance of pulmonary edema in cats . This study confirms and adds to the literature of the CT appearance of pulmonary edema in cats.…”
Section: Discussionsupporting
confidence: 91%
“…The CT findings of pulmonary edema described in our study were similar to the previously reported variable radiographic appearance of pulmonary edema in cats. 34 This study confirms and adds to the literature of the CT appearance of pulmonary edema in cats. This study also identified presumed severe diffuse pulmonary fibrosis, asthma (or chronic bronchitis), and a confirmed arterial thromboembolism.…”
Section: Resultssupporting
confidence: 85%
“…The utility of thoracic radiographs in distinguishing hydrostatic pulmonary edema from high‐permeability pulmonary edema has been evaluated in several studies, and the accuracy of this imaging modality is variable. This is especially true in cats, as they commonly display high variability in radiographic signs of congestive heart failure . Echocardiography is currently the gold standard to rule out hydrostatic pulmonary edema in veterinary medicine.…”
Section: Discussionmentioning
confidence: 99%
“…All of our patients had confirmed pulmonary lymphoma; however, pulmonary involvement is typically established in lymphoma patients when radiographic pulmonary changes are present, as other diagnostics are considered more invasive 1,2 . Based on our results, pulmonary lymphoma has a highly variable radiographic appearance; thus, differentials for abnormal pulmonary infiltrates in cats and dogs with multicentric or extranodal lymphoma can include neoplastic infiltration, pulmonary fibrosis, bacterial pneumonia, feline asthma, chronic bronchitis, and cardiogenic pulmonary edema 19 …”
Section: Discussionmentioning
confidence: 79%